Artesunate delays the dysfunction of age-related intestinal epithelial barrier by mitigating endoplasmic reticulum stress/unfolded protein response. (March 2023) - Chen, Hong; Sun, Hai-Mei; Wu, Bo; Sun, Ting-Yi; Han, Li-Zhuang; Wang, Guan; Shang, Yun-Fei; Yang, Shu; Zhou, De-Shan
Abstract: The impairment of the intestinal epithelial barrier and subsequent bacterial translocation are common in aging individuals, contributory to several local and systematic disorders. However, the underlying mechanism of the age-related degeneration has not been fully understood. In this study, we demonstrated that the intestinal KIT signaling declined and de-activated with aging, parallel with epithelial barrier dysfunction. Endoplasmic reticulum stress (ERS)/unfolded protein response (UPR) was obviously increased during aging. The ERS and its downstream IRE1α were highly activated in the aging colonic epithelium. Furthermore, by the use of Tunicamycin (Tm)-induced ERS mouse and cell models, we uncovered that the activity of the ERS/IRE1α accelerated the protein degradation of KIT via ubiquitin-proteasome pathway. The deficiency of KIT signaling further reduced the transcription of the tight junction protein Claudin-3. Of significance, Artesunate (ART) could be capable of ameliorating the detrimental effect of ERS/IRE1α, indicated by the re-gained KIT and Claudin-3 expressions and the restoration of the intestinal epithelial barrier. In conclusion, our present study provided novel evidence elucidating the ERS/IRE1α-induced loss of KIT and Claudin-3 in the aging colonic epithelium and also shed light on the protective effect of Artesunate on the intestinal epithelial barrier by blocking ERS/IRE1α activity during aging. Graphical Abstract: The ERS/IRE1α activity is provoked in the colonic epithelium during aging process, which down-regulates KIT via ubiquitin-proteasome pathway. The loss of KIT signaling inhibits the transcription of TJ protein Claudin-3. Altogether, the deficiency in KIT-Claudin-3 expression contributes to the impairment and dysfunction of the intestinal epithelial barrier and consequently the bacterial translocation. Artesunate is capable of restoring the integrity of the intestinal epithelial barrier by alleviating the ERS/IRE1α-induced down-regulation of KIT-Claudin-3 expression. ga1 Highlights: The ERS and its downstream IRE1α were highly activated in the colonic epithelium during aging. The activation of ERS/IRE1α induced the loss of KIT and Claudin-3 and impairment of the intestinal epithelial barrier. ERS/IRE1α accelerated the protein degradation of KIT via ubiquitin-proteasome pathway. Artesunate restored the integrity of the age-related intestinal epithelial barrier by alleviating ERS/IRE1α activity.